A Descriptive and Quantitative Immunohistochemical Study Demonstrating a Spectrum of Platelet Recruitment Patterns Across Pulmonary Infections Including COVID-19. Issue 3 (11th November 2020) - McMullen, Phillip D; Cho, Joseph H; Miller, Jonathan L; Husain, Aliya N; Pytel, Peter; Krausz, Thomas
Abstract: Objectives: Pulmonary platelet deposition and microangiopathy are increasingly recognized components of coronavirus disease 2019 (COVID-19) infection. Thrombosis is a known component of sepsis and disseminated intravascular coagulation. We sought to compare the level of platelet deposition in the pulmonary vasculature in cases of confirmed COVID-19 infection to other lung injuries and infections. Methods: Immunohistochemistry was performed on 27 autopsy cases and 2 surgical pathology cases targeting CD61. Multiple cases of normal lung, diffuse alveolar damage, COVID-19, influenza, and bacterial and fungal infections, as well as one case of pulmonary emboli, were included. The levels of CD61 staining were compared quantitatively in the autopsy cases, and patterns of staining were described. Results: Nearly all specimens exhibited an increase in CD61 staining relative to control lung tissue. The area of CD61 staining in COVID-19 infection was higher than influenza but still comparable to many other infectious diseases. Cases of aspiration pneumonia, Staphylococcus aureus infection, and blastomycosis exhibited the highest levels of CD61 staining. Conclusions: Platelet deposition is a phenomenon common to many pulmonary insults. A spectrum of staining patterns was observed, suggestive of pathogen-specific mechanisms of platelet deposition. Further study into the mechanisms driving platelet deposition in pulmonary injuries and infections is warranted.